THE IMPACT OF CHRONIC DISEASES ON THE PSYCHOSOMATIC STATE OF WOMEN IN THE CONTEXT OF ESCAPISM - Тодорцева, Юлія (SWorldJournal, 2026)
The article presents the results of an empirical study devoted to investigating the impact of chronic diseases on the psychosomatic state of women in the context of escapism. The relevance of the problem is determined by the prevalence of psychosomatic di